Post-Handover Housing Quality Management and Standards in Korea - Junmo Park; Deokseok Seo (Buildings, 2023)
Housing quality is a subject of dispute worldwide, and these disputes are increasing due to the significant differences in the views of producers and consumers on quality standards. To arbitrate disputes, an objective evaluation of housing quality is necessary. In Korea, disputes over housing quality in the post-handover stage result in lawsuits, thus becoming a social issue. This study analyzed the results of lawsuits against housing complexes in Korea. The ratio of defect repair cost to construction cost (DRCCC) was adopted as an indicator, and the quality level of the building was evaluated using a control chart to select failures. The findings showed that there were more cases where the construction cost was small, the housing quality was poor, the deviation was wide, and the quality defect exceeded the limit level of the control chart. To improve housing quality, it is necessary to strengthen quality management, to control the quality within the management limit, and to adjust standards by reflecting the consumer’s viewpoint.